Synthesis of Poly(thioester sulfonamide)s via the Ring‐Opening Copolymerization of Cyclic Thioanhydride with N‐Sulfonyl Aziridine Using Mild Phosphazene Base - Song, Peng‐Duo; Xia, Lei; Nie, Xuan; Chen, Guang; Wang, Fei; Zhang, Ze; Hong, Chun‐Yan; You, Ye‐Zi (Macromolecular rapid communications., 2022)
Providing access to diverse polymer structures is highly desirable, which helps to explore new polymer materials. Poly(thioester sulfonamide)s, combining both the advantages of thioesters and amides, however, are rarely available in polymer chemistry. Here, the ring‐opening copolymerization (ROCOP) of cyclic thioanhydride with N‐sulfonyl aziridine using mild phosphazene base, resulting in well‐defined poly(thioester sulfonamide)s with highly alternative structures, high yields, and controlled molecular weights, is reported. Additionally, benefiting from the mild catalytic process, this ROCOP can be combined with ROCOP of N‐sulfonyl aziridines with cyclic anhydrides to produce novel block copolymers. The ring‐opening copolymerization of cyclic thioanhydride with N‐sulfonyl aziridine using mild phosphazene base is reported, resulting in well‐defined poly(thioester sulfonamide)s with highly alternative structures, high yields, and controlled molecular weights.